2022
DOI: 10.1021/acsomega.1c06913
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Pore Structure and Fractal Characteristics of Different Lithofacies of Wufeng–Longmaxi Formation Shale in Southern Sichuan Basin, China

Abstract: Gas content and flow characteristics are closely related to shale lithofacies, and significant differences exist in the pore structure and fractal characteristics among lithofacies. In this study, X-ray diffractometer (XRD), field-emission scanning electron microscopy (FE-SEM), gas adsorption (N 2 and CO 2 ), and fractal theory were employed to systematically characterize the pore attributes of the marine Wufeng−Longmaxi formation shales. The information of various pores and microfractures among lithofacies wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…The relationship between shale composition and pore volumes shows that mesopore volumes had a moderate-strong positive correlation with TOC and carbonate content, while a moderate-weak negative correlation with quartz and clay content and macropore volumes had a moderate positive correlation with quartz content (Han et al, 2018). Both NMR and nitrogen adsorption show that organic pores are the main source of mesopores, which is consistent with previous studies proven by both qualitative and quantitative methods, such as N 2 gas adsorption and FE-SEM images (Yang et al, 2016;Han et al, 2018;He et al, 2021;Qian et al, 2022). Frontiers in Earth Science frontiersin.org…”
Section: Pore Type and Psd In Black Shalesupporting
confidence: 89%
“…The relationship between shale composition and pore volumes shows that mesopore volumes had a moderate-strong positive correlation with TOC and carbonate content, while a moderate-weak negative correlation with quartz and clay content and macropore volumes had a moderate positive correlation with quartz content (Han et al, 2018). Both NMR and nitrogen adsorption show that organic pores are the main source of mesopores, which is consistent with previous studies proven by both qualitative and quantitative methods, such as N 2 gas adsorption and FE-SEM images (Yang et al, 2016;Han et al, 2018;He et al, 2021;Qian et al, 2022). Frontiers in Earth Science frontiersin.org…”
Section: Pore Type and Psd In Black Shalesupporting
confidence: 89%
“…For Longmaxi Formation shales, the pore volume mainly comes from a large number of OM nanopores as well as inorganic mineral interpores and intrapores, where the micropores mainly contribute from the OM pores. The results of previous studies demonstrate that the micropore volume has a high correlation with the micropore surface area. ,,, In the present study, higher pore volume tended to indicate higher surface area, which could provide more oxygen-containing functional groups for adsorption, resulting in higher monolayer adsorption q 1 . At high Rh, both hydrophilic and hydrophobic pores take place capillary coalescence, forming large clusters of water molecules in the pore space, resulting in higher water adsorption.…”
Section: Resultssupporting
confidence: 58%
“…Ji et al observed that TOC can increase pore heterogeneity and the specific surface area, thereby producing a better positive correlation with the fractal dimension . Qian et al think that OM pores well developed in organic-rich siliceous shales provided more PV and SSA, and more complicated pore boundary of organic-rich shale . However, the shale samples from the Longmaxi Formation in this study have a high degree of OM maturity and have reached a late stage of over maturity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the OM-hosted pore is positively correlated with the gas content, which proves that the OM pores control the gas content (Figures 12C,D). Many studies have been conducted on the relationship between OM abundance and mineral content in deep marine shale (Li et al, 2022;Qian et al, 2022). It is generally agreed that clay minerals have a negative correlation with TOC, whereas brittle minerals have a positive correlation.…”
Section: Discussionmentioning
confidence: 99%